Evolution of teacher autonomy research: A systematic bibliometric analysis - Abdullah, Zuraidah; Yasin, Intan Rafidah; Abdul Razak, Ahmad Zabidi; Yasin, Nooni Ezdiani; Yasin, Nurul Ibtisyami (The S. Rajaratnam School of International Studies, 2024)
This bibliometric analysis examines the evolution of teacher autonomy research from 2013 to 2023, addressing the need for a comprehensive understanding of research trends, collaboration patterns, and knowledge distribution in this critical educational domain. Despite growing interest in teacher autonomy, there is limited systematic bibliometric analysis has previously mapped its development and identified key contributors across the global research landscape. Using bibliometric analysis techniques through Scopus database and VOSviewer visualisation tool, this study analysed publication patterns, citation impacts, geographical distributions, subject areas, and international collaborations. The analysis encompassed the manuscripts published between 2013 to 2023. Results reveal significant growth in publications, particularly post-2020, with the field nearly doubling from 40 (2013) to 102 publications (2023). The United States (113 publications) and United Kingdom (90 publications) emerge as leading contributors, while Social Sciences dominates subject areas (49.3%). Citation analysis identifies influential works focused on teacher well-being and technological integration. International collaboration networks show strong US-European partnerships and growing East-West research connections. The study concludes that teacher autonomy research is maturing into a globally collaborative, interdisciplinary field responsive to contemporary educational challenges. Future directions suggest expanding geographic representation, developing standardised measurement tools, and investigating emerging areas such as artificial intelligence’s impact on teacher autonomy.